THE RELATIONSHIP OF EMOTIONAL INTELLIGENCE, WORKPLACE CULTURE, AND NURSE PERFORMANCE IN A PRIVATE HOSPITAL IN MEDAN INDONESIA - Fajar Amanah Ariga; Jenny Marlindawani Purba; Mahnum Lailan Nasution (Belitung Nursing Journal, 2020)
Background: Nurse performance plays an important role in ensuring high quality care to achieve patient outcomes in hospitals. Therefore, factors related to the performance warrant investigation. Emotional intelligence and workplace culture are assumed to be related to nurse performance. Objective: To determine the relationship of emotional intelligence, workplace culture, and nurse performance at one of private hospitals in Medan Indonesia. Methods: This study employed a cross-sectional design with 126 associate nurses who were selected using a simple random sampling technique. Emotional intelligence, workplace culture, and nurse performance were measured using valid questionnaires. Spearman-Rank correlation test was used for data analysis. Results: Majority of nurses had high performance, emotional intelligence and workplace culture. There were significant relationships between emotional intelligence, workplace culture, and nurse performance, with a strong (r= .68; p= .01) and medium level (r= .30; p= .01), respectively. Conclusion: Nurses with high emotional intelligence and good workplace culture would show good performance in providing professional nursing care to patients. It is recommended for the hospital managers and nurse managers to improve emotional intelligence of nurses and create better workplace culture in order to improve the nurse performance.